PENGEMBANGAN EKONOMI ISLAM SEBAGAI DISIPLIN ILMU - Joko Hadi Purnomo (Al Hikmah: Jurnal Studi Keislaman, 2020)
Islamic economics emerged in the 70s decade and continues to develop until the 21st century, but various challenges in the development of Islamic Economics became a discipline that was developed by itself well-established and sturdy. There are three main criteria for bringing Islamic Economics into a scientific discipline, namely a philosophical foundation that complements the ontological, epistemological, axioglogic foundation; Islamic Economic System and Islamic Economic Policy. As a building of Islamic Economics, it has sufficient capital, because there are parts that meet the criteria that are completely different from Western Economics, but there are parts that still need to be further developed because they are not rooted in Islam. . Development of Islamic Economics into buildings that must be resolved in solving problems relating to the economy that develops in the economic field and conceptual economics of Islamic Economics; The epistemological foundation of Islamic Economics determines the concept of Islamic Economics and understands Islamic Economics; Ethical (axiological) foundation; Developing an Islamic Economy can be made as an economic system and used as a country's public policy. Keywords: body of knowledge, ontological, epistemological, axiology